Pollution Pattern in the Mokuro Dam in Ile-Ife - Petters, Hannah Itam (Obafemi Awolowo University, 2014)
Bacteriological and physical-chemical analyses of the Mokuro Jam (in Ile-Ife) an its distribution system were carried out from December 1982 to November 1983 at monthly intervals, and the quality of water was assessed to establish the pollution pattern.